A sliding technique to load thin endothelial donor lamella onto Busin glide for Descemet-stripping automated endothelial keratoplasty - Kobayashi A (Dove Medical Press, 2012)
Akira Kobayashi, Hideaki Yokogawa, Kazuhisa SugiyamaDepartment of Ophthalmology, Kanazawa University Graduate School of Medical Science, Kanazawa, JapanAbstract: We describe a modified technique for loading donor corneal endothelial lamella onto a Busin glide® without causing wrinkles, as part of the procedure of Descemet-stripping automated endothelial keratoplasty. Briefly, after punching out a composite of the donor-endothelial lamella and a microkeratome-dissected cap, several drops of dispersive ophthalmic viscosurgical device are placed onto the endothelial surface. The Busin glide surface is then wetted with several drops of balanced salt solution. After the composite is transferred onto the Busin glide, hydrodissection of the potential space between the donor-endothelial lamella and the microkeratome-dissected cap is carefully performed to enable smooth detachment of these two lamellae. Whereas simply dragging the donor-endothelial lamella directly onto the glide can cause wrinkling or folding of the donor lamella, this technique enables smooth detachment of the composite without wrinkle or fold formation, and results in less endothelial cell damage.Keywords: DSAEK, Busin glide, endothelial keratoplasty